Vascular anomalies. Issue 6 (June 2018) - Gokani, Vimal J.; Sivakumar, Branavan; Kangesu, Loshan
Abstract: Vascular anomalies are vascular lesions, present from childhood. They are classified into tumours or malformations based on clinical and histological features. Benign infantile haemangiomas are the most common vascular tumour and have a predictable self-limiting course. Management is conservative, with active treatment reserved for the presence of functional or cosmetic complications (ulceration, obstruction and distortion of vital structures). Oral propranolol is useful for troublesome lesions. Rarer tumours may cause platelet consumption. Vascular malformations are structural anomalies of vascular morphogenesis, present at birth, without cellular proliferation that, in general, grow with the patient. They are subclassified by vessel type as low flow (capillary, lymphatic and venous) and high flow (arteriovenous), or lesions with combinations of vessel types. They may become problematic at puberty or during pregnancy. Extensive venous and arteriovenous lesions are the most troublesome. Their effects may be cosmetic, or those of a space-occupying lesion: infection, bleeding, pain or coagulopathy. Venous lesions cause consumptive coagulopathy, sometimes with life threatening risks. Treatment options include medication and symptomatic control with antibiotics, analgesia, control of menses, compression garments, laser intervention, interventional radiology (sclerotherapy and embolization) and surgery. Patients with complex lesions, are best managed by a multidisciplinary team.